Measurements of tt[over ¯]H Production and the CP Structure of the Yukawa Interaction between the Higgs Boson and Top Quark in the Diphoton Decay Channel - Sirunyan, A M; Tumasyan, A; Adam, W; Ambrogi, F; Bergauer, T; Dragicevic, M; Erö, J; Escalante Del Valle, A; Flechl, M; Frühwirth, R; Jeitler, M; Krammer, N; et al. (Physical review letters, 2020)
The first observation of the tt[over ¯]H process in a single Higgs boson decay channel with the full reconstruction of the final state (H→γγ) is presented, with a significance of 6.6 standard deviations (σ). The CP structure of Higgs boson couplings to fermions is measured, resulting in an exclusion of the pure CP-odd structure of the top Yukawa coupling at 3.2σ. The measurements are based on a sample of proton-proton collisions at a center-of-mass energy sqrt[s]=13 TeV collected by the CMS detector at the LHC, corresponding to an integrated luminosity of 137 fb^{-1}. The cross section times branching fraction of the tt[over ¯]H process is measured to be σ_{tt[over ¯]H}B_{γγ}=1.56_{-0.32}^{+0.34} fb, which is compatible with the standard model prediction of 1.13_{-0.11}^{+0.08} fb. The fractional contribution of the CP-odd component is measured to be f_{CP}^{Htt}=0.00±0.33.